A monument to socialist industrialisation or a tool for creating urban development? Rehabilitation of former industrial tram lines (FITL) in Central-Eastern Europe after socialist industrialisation in the context of transit oriented development - Taczanowski, Jakub; Kołoś, Arkadiusz; Fiedeń, Łukasz (Cities, 2026)
The purpose of the paper is to answer the question whether and how former industrial tram lines (FITL) can be useful in the context of urban development and whether their transformation can be compatible with the TOD concept. FITL are tram lines constructed in order to transport large numbers of workers to enormous industrial plants which were characteristic for socialist urban planning in Central-Eastern Europe (CEE). Among 21 FITL identified in four CEE countries (Poland, Czechia, Slovakia and Hungary), 14 % have witnessed a large scale functional transformation in their neighbourhoods with a total termination of industrial activity, accompanied by revitalisation of the tram infrastructure. In the case of another 43 % at least a partial neighbourhood revitalisation has taken place while the remaining lines are still waiting for new functions. We argue that under the influence of specific factors FITL can be transformed into modern urban solutions which under favourable circumstances can be compatible with the concept of Transit Oriented Development (TOD). The most important of these factors include ease adaptability of the area for new functions, good accessibility and lack of too negative image of the postindustrial area as well as polyfunctional character of the city and its high position in the settlement hierarchy, accompanied by coherent transport and spatial policy promoting mixed urban development and public transport. For TOD to happen it is crucial that the tram line has an active role in the functional transformation process, being modernised and adjusted to a new role. It cannot be overstated that appropriate approach to urban and transport planning is a crucial success factor here. •Former Industrial Tram Lines (FITL) have a potential to be utilised for modern urban development•Over 50 % of FITL in Central-Eastern Europe have witnessed some kind of functional transformation•Main conditions of a successful transformation are urban pattern and general potential of the city•FITL transformation can be compatible with TOD if the tram line has an active role in this process